Volatility dynamics of NYMEX natural gas futures prices - Suenaga, Hiroaki; Smith, A.; Williams, J. (Wiley InterScience, 2008)
We examine the volatility dynamics of NYMEX natural gas futures prices via the partially overlapping time-series model of Smith (2005, Journal of Applied Econometrics, 20, 405-422). We show that volatility exhibits two important features: (1) volatility is greater in the winter than in the summer, and (2) the persistence of price shocks and, hence, the correlations among concurrently traded contracts, displays substantial seasonal and cross-sectional variation in a way consistent with the theory of storage. We demonstrate that, by ignoring the seasonality in the volatility dynamics of natural gas futures prices, previous studies have suggested sub-optimal hedging strategies.